2022
DOI: 10.1002/anie.202211952
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthetic C−O Bond Activation in Alcohols and Alcohol Derivatives

Abstract: Alcohols and their derivatives are ubiquitous and versatile motifs in organic synthesis. Deoxygenative transformations of these compounds are often challenging due to the thermodynamic penalty associated with the cleavage of the CÀ O bond. However, electrochemically driven redox events have been shown to facilitate the CÀ O bond cleavage in alcohols and their derivatives either through direct electron transfer or through the use of electron transfer mediators and electroactive catalysts. Herein, a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 245 publications
0
25
0
Order By: Relevance
“…44 The vicinal aromatic system is expected to result in enhanced thermodynamic stability of benzylic carbocations compared to carbocations that would result from primary aliphatic alcohols and phenols. This stability difference is reflected in the associated C-OH bond dissociation energies of the parent alcohols 56 and is demonstrated by the selective etherification of 1b at the benzylic position while the phenolic and γ-OH groups remain unreacted. Using the optimised reaction conditions, a series of ethers were synthesized with different functionalities on the ether side chain (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…44 The vicinal aromatic system is expected to result in enhanced thermodynamic stability of benzylic carbocations compared to carbocations that would result from primary aliphatic alcohols and phenols. This stability difference is reflected in the associated C-OH bond dissociation energies of the parent alcohols 56 and is demonstrated by the selective etherification of 1b at the benzylic position while the phenolic and γ-OH groups remain unreacted. Using the optimised reaction conditions, a series of ethers were synthesized with different functionalities on the ether side chain (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…23 As such, the work showcased an alternative electroreductive transformation of esters compared to the Bouveault–Blanc reaction (acyl C–O bond cleavage) and the Markó–Lam reaction (carboxyl C–O bond cleavage). 24 The electrochemical reactions were carried out in an undivided cell equipped with a sacrificial magnesium anode and a nickel foam cathode with SmCl 3 (10 mol%) at 20 °C under an argon atmosphere (Scheme 6 ). Using standard conditions, phenyl benzoate was converted into the corresponding 1,2-diketone in 85% yield, whereas arene substrates possessing fluoride or nitrile substituents resulted in yields of 55% and 50%, respectively.…”
Section: Compounds Containing Carbon–oxygen Bondsmentioning
confidence: 99%
“…Reaction of F with another alkyl halide ( G ) results in the formation of a new C–C bond and furnishes cross-electrophile coupling (XEC) product H . We were interested in developing an analogous electrochemical strategy for the deoxygenative functionalization of alcohols, aldehydes, and ketones, in which substrates with their native functional groups can be directly employed in the reaction via in situ activation. Here, we present such an approach using pinacolborane (HBpin) as both an activator and a reactant (Scheme C).…”
mentioning
confidence: 99%
“…13 In previous work (Scheme 2A, upper), we showed that at a sufficiently reducing potential, an alkyl halide (A) can undergo a sequence of electron transfer−chemical reaction−electron transfer (ECE) processes that results in cleavage of the C−X bond to form a carbanion intermediate (F). 14 Reaction of F with another alkyl halide (G) results in the formation of a new C−C bond and furnishes cross-electrophile coupling (XEC) product H. We were interested in developing an analogous electrochemical strategy for the deoxygenative functionalization of alcohols, 15 aldehydes, and ketones, in which substrates with their native functional groups can be directly employed in the reaction via in situ activation. Here, we present such an approach using pinacolborane (HBpin) as both an activator and a reactant (Scheme 1C).…”
mentioning
confidence: 99%